On the organization of the diplomatic service in the post-Horde Chingisid states in the 16th century (Crimean and Kazan khanates): “tets” and “bakshis” - Moiseev M.V. (Золотоордынское обозрение)
Research objectives: This study investigates the development of the embassy service in the post-Horde states, with a specific focus on identifying its structure and analyzing its personnel composition. Research materials: The research primarily relies on the analysis of Russian embassy books and chronicles. Results and novelty of the research: The examination of Russian documents reveals that Khan’s embassies followed a three-part structure: Ambassador (elchi)-deputy (tet)-secretary (bakshi). The Russian chancellery was notably reluctant to use the term “tet,” likely because individuals with this title were responsible for collecting specific duties from Russian lands in favor of the Khan. It is possible that the Russian documents referred to the “tet” as a toll collector; in any case, we know that ambassadors could be accompanied by “toll collectors.” After 1475, these duties were abolished. In total, 7 mentions of Crimean tets and 6 Kazan tets were identified. References to baksheys in embassies are better preserved, with a total of 18 Crimean, 8 Kazan, 2 Nogai, and 1 Siberian bakshi identified. One of the primary responsibilities of baksheys was to compile a certificate. Thus, the observation of the embassy mission’s composition relies on source-based evidence. Even when there is no specific information about shoring, the mere presence of a bakshey serves as a reliable indicator that the outcome of the negotiations was expected to involve shoring. The study reveals that we can discuss the process of forming the diplomatic service in the post-Horde Chingisid states.